Image Branding Destination Pembangunan Desa Wisata di Objek Wisata Sendang Senjoyo Salatiga, Semarang - Susanti, Endang; Utami, Noviandari Sari; Sholeh, Muhammad (LUGAS Jurnal Komunikasi, 2022)
The image of tourism destinations has become the focus of research in recent decades. Tourism has an important role in the economies of developing countries that depend on tourism revenues as the main source of income. The tourism industry players are trying hard to attract more tourists and increase tourism revenue, in which the competition among these destinations is increasing day by day. Sendang Senjoyo is one of the tourism objects located in Tegal Weton Village, Tingkir District, Salatiga Regency, Semarang. This tourist attraction offers a spring tour known as the Spring Senjoyo spring or Umbul Senjoyo which promises natural beauty with a cool atmosphere and the freshness of the clear water.This research method uses a qualitative descriptive approach, the purpose of this study is to find out how the Image Branding Destination for Tourism Village Development in Senjang Senjoyo Tourism Object, Salatiga. The resource persons taken in this study amounted to 3 people consisting of the Head of Tegalwaton Village, Semarang Regency, the tourism object manager (BUMDES) Sendang Senjoyo, and the surrounding community or tourists. The results of this study indicate that the management of the Senjoyo tourist attraction is carried out by the Tegalwaton Village government in collaboration with the Village-Owned Enterprises (BUMDES) and local communities. Image Branding Destination Sendang Senjoyo tourist attraction was built with the concept of spiritual, nature, entertainment, tree museum and springs. The lack of facilities and infrastructure at the Senjang Senjoyo tourist attraction which is still not optimal and not functioning properly, as well as the absence of natural resource development for tourism object managers to be given training in improving the ability to manage tourist attractions.Keywords:,The image of tourism destinations has become the focus of research in recent decades. Tourism has an important role in the economies of developing countries that depend on tourism revenues as the main source of income. The tourism industry players are trying hard to attract more tourists and increase tourism revenue, in which the competition among these destinations is increasing day by day. Sendang Senjoyo is one of the tourism objects located in Tegal Weton Village, Tingkir District, Salatiga Regency, Semarang. This tourist attraction offers a spring tour known as the Spring Senjoyo spring or Umbul Senjoyo which promises natural beauty with a cool atmosphere and the freshness of the clear water.This research method uses a qualitative descriptive approach, the purpose of this study is to find out how the Image Branding Destination for Tourism Village Development in Senjang Senjoyo Tourism Object, Salatiga. The resource persons taken in this study amounted to 3 people consisting of the Head of Tegalwaton Village, Semarang Regency, the tourism object manager (BUMDES) Sendang Senjoyo, and the surrounding community or tourists. The results of this study indicate that the management of the Senjoyo tourist attraction is carried out by the Tegalwaton Village government in collaboration with the Village-Owned Enterprises (BUMDES) and local communities. Image Branding Destination Sendang Senjoyo tourist attraction was built with the concept of spiritual, nature, entertainment, tree museum and springs. The lack of facilities and infrastructure at the Senjang Senjoyo tourist attraction which is still not optimal and not functioning properly, as well as the absence of natural resource development for tourism object managers to be given training in improving the ability to manage tourist attractions.